Traditional Community Participation Model in Conflict Resolution among Two Mining Companies - Gajah, Nurhamidah; Sitorus, Henry; Sihombing, Marlon; Arifana, Arifana; Pasaribu, Safran Efendi (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Mining operations in North Sumatera Province have generated both economic opportunities and socio-environmental challenges for surrounding traditional communities. The coexistence of PT. Agincourt Resources in Batangtoru and PT. Sorikmas Mining in Naga Juang has triggered land disputes, environmental degradation, and social polarization, reflecting the tension between corporate expansion and the preservation of customary (adat) values.Purposes of the Research: This study aims to map and classify sources of social conflict between mining companies and local adat communities, examine the dynamics of traditional institutions, and develop a participatory conflict resolution model that integrates local wisdom and community empowerment.Methods of the Research: Using a mixed-method design, this research combines quantitative surveys with qualitative approaches, including in-depth interviews, focus group discussions, and participant observation. Data were analyzed using parametric statistics and qualitative matrix analysis to identify socio-cultural dynamics, conflict patterns, and the institutional role of adat in mediating disputes.Results of the Research: The findings show that mining activities have disrupted social cohesion and traditional governance structures, particularly regarding ulayat (customary) land rights. Nonetheless, the study introduces a Traditional Community Participation Model emphasizing adat leaders as mediators in conflict resolution. This model reinforces social capital, restores trust, and enhances collaboration between companies, communities, and government institutions. The research offers a novel integrative framework linking customary institutions with sustainable conflict management and responsible mining governance in Indonesia.